Structures, electronic properties and stability phase diagrams for copper(i/ii) bromide surfaces. Issue 14 (14th April 2015) - Altarawneh, Mohammednoor; Marashdeh, Ali; Dlugogorski, Bogdan Z.
<x xml:space="preserve">Abstract</x> This study presents a comprehensive periodic slab DFT investigation into structures, electronic properties and thermodynamic stability of all plausible terminations of CuBr and CuBr2 surfaces. We find that surfaces terminated with negatively charged bromine atoms tend to be more stable if they are accompanied by significant relaxation.